Mitigation of antinutritional factors and protease inhibitors of defatted winged bean-seed proteins using thermal and hydrothermal treatments: denaturation/unfolding coupled hydrolysis mechanism - Saadi, Sami; Saari, Nazamid; Mohd Ghazali, Hasanah; Abdulkarim, Mohammed Sabo (Elsevier BV, 2022)
The inactivation of antinutritional factors, protease inhibitors within winged bean protein was induced by two respective method treatments. The physical method based on steam vapor that was conducted using an autoclave and chemical method consisting on pH-gradients of buffer solutions prepared at respective acidic pH, neutral pH and alkaline pH ranges. The activity of remaining protease inhibitors of bowman birk inhibitor (BBI), and kunitz-trypsin inhibitor (KTI) after and before treatments was enzymatically confirmed using relevant antagonistic trypsin and combined trypsin-α-chymotrypsin digests. The resulting molecular assembly indicating an interval molecular relaxation range of °0.16 < °DA < °0.2 corresponding to reconformation in protein units with volume-mass changes of −2.17 < ∂v' < +2.17 and with denaturation/unfolding efficiency based on heat capacity ΔCp of 36.36 < DE/UF% < 54.67. These structural changes had a great benefit in determining and producing functional protein hydrolysates.